Cu1-xRExO (RE = La, Dy) decorated dendritic CuS nanoarrays for highly efficient splitting of seawater into hydrogen and oxygen fuels. (September 2021) - Rodney, John D; Deepapriya, S.; Robinson, M. Cyril; Das, S. Jerome; Perumal, Suresh; Sivakumar, Periyasamy; Jung, Hyun; Kim, Byung Chul; Raj, C. Justin
Highlights: Seawater splitting was carried out using Cu1-x REx O as the electrocatalyst. OER activity was found to be 1.57 V vs RHE@10 mAcm −2 in seawater + 1M KOH HER activity was found to be -0.17 V vs RHE@-10 mAcm −2 in seawater + 1M KOH Electrocatalyst was also subjected to 6M KOH + 1.5M NaCl@80°C (harsh) Abstract: Electrochemical water splitting has considered as an attractive technique in generating clean hydrogen fuel as secondary energy storage. For large-scale production of hydrogen, electrolysis of seawater is considered to the replacement for fresh water due to its natural abundance. However, the alternation requires the development of a robust and cheap electrocatalyst that can perform seawater splitting without undergoing any chloride corrosion at the anode surface. Herein we fabricated a bi-layered anode with dysprosium doped copper oxide (Cu0.98 Dy0.02 O) electrocatalyst layer coated copper sulfide (CuS) nanodendritic over stainless steel (SS) substrate for Oxygen Evolution Reaction (OER). This optimized bi-layered anode exhibited a superior OER activity posting a potential of 1.57 V vs RHE to achieve the benchmark current density of 10 mA cm −2 in real seawater + 1 M KOH electrolyte without chloride corrosion. On the other hand, a lanthanum doped copper oxide (Cu0.98 La0.02 O) electrocatalyst layer on a stainless-steel substrate act as a cathode for Hydrogen Evolution Reaction (HER) and exhibited a superior HER activity with a potential of -0.176 V vs RHE to achieve the standard current density in real seawater + 1 M KOH electrolyte. Significantly, the combination of these two electrodes achieved overall alkaline seawater splitting with a cell voltage of 1.53 V to attain the benchmark current density. In addition, long term stability of 12 h was achieved at a low cell voltage of 2.23 V for a current density of 50 mA cm −2 with 100% retention capability. This result demonstrates the advancement in the development of cheaper electrocatalysts for seawater splitting in large-scale hydrogen production. Graphical Abstract: Image, graphical abstract